Biotechnological Potential of Microorganisms for Mosquito Population Control and Reduction in Vector Competence - Katak, Ricardo de Melo; Cintra, Amanda Montezano [UNESP]; Burini, Bianca Correa; Marinotti, Osvaldo; Souza-Neto, Jayme A. [UNESP]; Rocha, Elerson Matos [UNESP] (MDPI, 2023)
Mosquitoes transmit pathogens that cause human diseases such as malaria, dengue fever, chikungunya, yellow fever, Zika fever, and filariasis. Biotechnological approaches using microorganisms have a significant potential to control mosquito populations and reduce their vector competence, making them alternatives to synthetic insecticides. Ongoing research has identified many microorganisms that can be used effectively to control mosquito populations and disease transmission. However, the successful implementation of these newly proposed approaches requires a thorough understanding of the multipronged microorganism–mosquito–pathogen–environment interactions. Although much has been achieved in discovering new entomopathogenic microorganisms, antipathogen compounds, and their mechanisms of action, only a few have been turned into viable products for mosquito control. There is a discrepancy between the number of microorganisms with the potential for the development of new insecticides and/or antipathogen products and the actual available products, highlighting the need for investments in the intersection of basic research and biotechnology.
Keywords: bacteria; biotechnology; fungi; microorganisms; mosquitoes; vector control